PERMANENT ECONOMIC DISORDER - Karimzadi, Shahzavar ([S.l.] : ROUTLEDGE, 2022)
All schools of thought in economics, explicitly or otherwise, have referred to economic disorder as a self-evident fact. They have also unanimously considered it to be a temporary state. By contrast, this book contends that economic disorder is an interminable condition of human existence. From this perspective, the present study brings to light the misunderstanding of successive generations of economists on economic disorders. This book provides an alternative exposition of economic disorder and correctional measures that can be taken in order to correct these misconceptions. The analysis offered in this book is a scholarly work that provides a thorough explanation of the hidden dimensions and multiple aspects of economic disorders. Much of this book is devoted to uncovering the origins of such dimensions to further refine our understanding of the development of contemporary economies. To this end, this book also outlines how to tackle some of the most intriguing issues of our time. It seeks to provide a refreshing recount of the tenets of economic disorders. This book is a major contribution to the literature on economic disorder and crises and will be of great interest to readers of economic theory, philosophy of economics and the history of economic thought.
Keywords: Economics; Economic history; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General